Tuberculosis in Scottish military veterans: evidence from a retrospective cohort study of 57 000 veterans and 173 000 matched non-veterans. Issue 1 (22nd March 2016) - Bergman, Beverly P; Mackay, DF; Pell, JP
Abstract : Objective: Tuberculosis was a major cause of morbidity and manpower loss in the Armed Forces during World War II. Military control programmes commenced in the 1950s but were initially limited in scope by the many recruits who were already tuberculin positive on enlistment. The aim of our study was to examine whether veterans have an increased risk of tuberculosis compared with non-veterans. Methods: Retrospective cohort study of 57 000 veterans born 1945–1985, and 173 000 people with no record of military service, resident in Scotland, matched for age, sex and area of residence, using Cox proportional hazard analysis to compare the risk of tuberculosis overall, by birth cohort, length of service and year of diagnosis and to examine comorbidities. Results: Over mean 29 years follow-up, 69 (0.12%) veterans were recorded as having tuberculosis, compared with 267 (0.15%) non-veterans (unadjusted HR 0.90, 95% CIs 0.69 to 1.19, p=0.463). Only the 1945–1949 veterans' birth cohort was at higher risk, unadjusted HR 1.54, 95% CIs 0.98 to 2.45, p=0.061, although the difference in risk did not achieve significance. Veterans born from 1950 were at significantly reduced risk of tuberculosis compared with non-veterans after adjusting for deprivation, HR 0.67, 95% CI 0.47 to 0.95, p=0.026. The most common comorbidities were smoking-related and alcohol-related disease. The risk of comorbid hepatitis B or C was very low, in both veterans and non-veterans. No length of service was associated with an increased risk of tuberculosis in comparison with non-veterans. Conclusions: Scottish veterans born before 1950 are at moderately increased risk of tuberculosis compared with age, sex and geographically matched civilians with no record of service, although the difference is not statistically significant. Scottish veterans born from 1950 show a reduction in risk compared with civilians. Tuberculosis should be considered in the differential diagnosis of respiratory disease in the older veteran.